PENERAPAN METODE TRANSPORTASI NORTH WEST CORNER TERHADAP OPTIMALISASI DISTRIBUSI LAYANAN MAXIM CAR - Yusuf Wasanggai; Heru Sutejo; Rosana Deda; Heni Murib; Febrian Baru (Jurnal Ekonomi dan Bisnis, 2026)
This Study Aims To Analyze The Optimization Of Maxim Car Service Distribution In The Areas Of Waena, Abepura, And Entrop Using The North West Corner Method. This Method Was Used To Determine A More Efficient Service Distribution Pattern Based On The Balance Between Supply And Demand In Each Operational Area. The Research Was Conducted By Collecting Data On Driver Capacity And Customer Service Demand, Which Were Then Processed Using QM For Windows. The Result Showed That The Implemention Of North West Corner Method Was Able To Produce A More Optimal Service Distribution Allocation With A Total Distribution Cost Of Rp 5,320,000 Over 24 Operational Hours. In Addition, This Method Helped Reduce Imbalances In Service Distribution, Improve Operational Efficiency, And Simplify Decision Making Related Tpoo Allocation Of Online Transportasion  Service. Therefore , The North West Corrner Methodf Can Be Considered  Ann Effective Solution For Optimizing Online Trasportasi Service Distribution, Particulary For Maxim Car Service In Jayapura City